Fe(III) complex of biuret-amide based macrocyclic ligand as peroxidase enzyme mimic - Panda, Chakadola; Ghosh, Munmun; Panda, Tamas; Banerjee, Rahul; Sen Gupta, Sayam (Chemical Communications, 2011)
An Fe(III) complex of a biuret-amide based macrocyclic ligand that exhibits both excellent reactivity for the activation of H(2)O(2) and high stability, especially at low pH and high ionic strength, is reported.

One pot glucose detection by [Fe-III(biuret-amide)] immobilized on mesoporous silica nanoparticles: an efficient HRP mimic - Malvi, Bharmana; Panda, Chakadola; Dhar, Basab B.; Sen Gupta, Sayam (Chemical Communications, 2012)
An [Fe-III(biuret-amide)] complex has been immobilized onto mesoporous silica nanoparticles via Cu(I) catalyzed azide-alkyne click chemistry. This hybrid material functions as an efficient peroxidase mimic and was successfully used for the quantitative determination of hydrogen peroxide and glucose via a one-pot colorimetric assay.

Synthesis of functional hybrid silica scaffolds with controllable hierarchical porosity by dynamic templating - Ganai, Anal Kumar; Kumari, Sushma; Sharma, Kamendra P.; Panda, Chakadola; Kumaraswamy, Guruswamy; Sen Gupta, Sayam (Chemical Communications, 2012)
We report a facile one-pot synthesis of hierarchically porous scaffolds, with independent control over nanoparticle mesoporosity and scaffold macroporosity. Our technique combines the chemistry of mesoporous silica nanoparticles with the control afforded by dynamic templating of surfactant mesophases. These materials are readily functionalizable and allow controllable spatial variation in macroporosity.

Catalytic signal amplification using [Fe-III(biuret-amide)]-mesoporous silica nanoparticles: visual cyanide detection - Panda, Chakadola; Dhar, Basab B.; Malvi, Bharmana; Bhattacharjee, Yudhajit; Sen Gupta, Sayam (Chemical Communications, 2013)
Catalytic signal amplification was used for the colorimetric detection of CN- in aqueous media by using the enzyme catalase in tandem with mesoporous silica nanoparticle based synthetic HRP enzyme mimic Fe-MSNs. Signal amplification up to a maximum of eight fold was observed for the reporter ``oxidized TMB'' with respect to the added CN- ion.

Fe-TAML encapsulated inside mesoporous silica nanoparticles as peroxidase mimic: femtomolar protein detection - Kumari, Sushma; Dhar, Basab B.; Panda, Chakadola; Meena, Abhishek; Sen Gupta, Sayam (ACS Applied Materials & Interfaces, 2014)
Peroxidase, such as horseradish peroxidase (HRP), conjugated to antibodies are routinely used for the detection of proteins via an ELISA type assay in which a critical step is the catalytic signal amplification by the enzyme to generate a detectable signal. Synthesis of functional mimics of peroxidase enzyme that display catalytic activity which far exceeds the native enzyme is extremely important for the precise and accurate determination of very low quantities of proteins (fM and lower) that is necessary for early clinical diagnosis. Despite great advancements, analyzing proteins of very low abundance colorimetrically, a method that is most sought after since it requires no equipment for the analysis, still faces great challenges. Most reported HRP mimics that show catalytic activity greater than native enzyme (similar to 40-fold) are based on metal/metal-oxide nanoparticles such as Fe3O4. In this paper, we describe a second generation hybrid material developed by us in which approximately 25 000 alkyne tagged biuret modified Fetetraamido macrocyclic ligand (Fe-TAML), a very powerful small molecule synthetic HRP mimic, was covalently attached inside a 40 nm mesoporous silica nanopartide (MSN). Biuret-modified Fe-TAMLs represent one of the best small molecule functional mimics of the enzyme HRP with reaction rates in water close to the native enzyme and operational stability (pH, ionic strength) far exceeding the natural enzyme. The catalytic activity of this hybrid material is around 1000-fold higher than that of natural HRP and 100-fold higher than that of most metal/metal oxide nanoparticle based HRP mimics reported to date. We also show that using antibody conjugates of this hybrid material it is possible to detect and, most importantly, quantify femtomolar quantities of proteins colorimetrically in an ELISA type assay. This represents at least 10-fold higher sensitivity than other colorimetric protein assays that have been reported using metal/metal oxide nanoparticles as HRP mimic. Using a human IgG expressing cell line, we were able to demonstrate that the protein of interest human IgG could be detected from a mixture of interfering proteins in our assay.
Keywords: colorimetrically; immuno assay; MSN; peroxidase mimic; signal amplification

Formation of a room temperature stable Fe-V(O) complex: reactivity toward unactivated C-H bonds - Ghosh, Munmun; Singh, Kundan K.; Panda, Chakadola; Weitz, Andrew; Hendrich, Michael P.; Collins, Terrence J.; Dhar, Basab B.; Sen Gupta, Sayam (Journal of American Chemical Society, 2014)
An Fe-V(O) complex has been synthesized from equimolar solutions of (Et4N)(2)[Fe-III(Cl)(biuretamide)] and mCPBA in CH3CN at room temperature. The Fe-V(O) complex has been characterized by UV-vis, EPR, Mossbauer, and HRMS and shown to be capable of oxidizing a series of alkanes having C-H bond dissociation energies ranging from 99.3 kcal mol(-1) (cyclohexane) to 84.5 kcal mori (cumene). Linearity in the Bell-Evans-Polayni graph and the finding of a large kinetic isotope effect suggest that hydrogen abstraction is engaged the rate-determining step.

Homogeneous photochemical water oxidation by biuret-modified Fe-TAML: evidence of Fe-V(O) intermediate - Panda, Chakadola; Debgupta, Joyashish; Diaz, David Diaz; Singh, Kundan K.; Gupta, Sayam Sen; Dhar, Basab B. (Journal of the American Chemical Society, 2014)
{Water splitting, leading to hydrogen and oxygen in a process that mimics natural photosynthesis, is extremely important for devising a sustainable solar energy conversion system. Development of earth-abundant, transition metal-based catalysts that mimic the oxygen-evolving complex of photosystem II, which is involved in oxidation of water to O-2 during natural photosynthesis, represents a major challenge. Further, understanding the exact mechanism, including elucidation of the role of active metal-oxo intermediates during water oxidation (WO), is critical to the development of more efficient catalysts. Herein, we report Fe-III complexes of biuret-modified tetra-amidomacrocyclic ligands (Fe-TAML; 1a and 1b) that catalyze fast, homogeneous, photochemical WO to give OD with moderate efficiency (maximum TON = 220

Molecular Fe-complex as a catalyst probe for in-gel visual detection of proteins via signal amplification - Kumari, Sushma; Panda, Chakadola; Mazumdar, Shyamalava; Sen Gupta, Sayam (Chemical Communications, 2015)
We report the use of a molecular peroxidase mimic biuret-Fe-TAML for chemoselective labeling of proteins and the subsequent visual detection (<0.1 pmoles) of the conjugate in a polyacrylamide gel by catalytic signal amplification. Use of this probe in activity based protein profiling (ABPP) of serine proteases is also demonstrated.

Reactivity and operational stability of N-Tailed TAMLs through kinetic studies of the catalyzed oxidation of orange II by H2O2: synthesis and x-ray structure of an N-Phenyl TAML - Warner, Genoa R.; Mills, Matthew R.; Enslin, Clarissa; Pattanayak, Shantanu; Panda, Chakadola; Panda, Tamas Kumar; Sen Gupta, Sayam; Ryabov, Alexander D.; Collins, Terrence J. (Chemistry A-European Journal, 2015)
{The catalytic activity of the N-tailed (biuret) TAML (tetraamido macrocyclic ligand) activators [Fe{4-XC6H3-1,2-(NCOCMe2NCO)(2)NR}Cl](2-) (3; N atoms in boldface are coordinated to the central iron atom; the same nomenclature is used in for compounds 1 and 2 below), [X
Keywords: Hydrogen peroxide; iron; kinetics; Oxidation; reaction mechanisms